Effect of partial pulp removal and fermentation duration on drying behavior, nib acidification, fermentation quality, and flavor attributes of Ghanaian cocoa beans - Lukeman Haruna; Ernest E. Abano; Ernest Teye; Isaac Tukwarlba; Stephen Adu; Kesse J. Agyei; Eric Kuma; Wilson Yeboah; Mary Lukeman (Journal of Agriculture and Food Research, 2024)
The study investigated the impact of partial pulp removal (PPR) and fermentation duration (FD) on drying behavior, quality attributes and flavor profile of cocoa beans. The research explored the use of PPR (ranging from 0 % to 100 %) at various FDs (0–6 days) as potential pulp pre-conditioning technique to enhance the drying time, pH, titratable acidity (TTA), fermentation quality (FQ), fermentation index (FI), and flavor attributes of fermented and sun-dried Ghanaian cocoa beans. The results revealed a significant reduction in drying time from 144 to 4.3 h for the 6 days fermented beans subjected to 0–100 % PPR treatment. Nib pH levels increased from 5.28 to 5.74, while the nib TTA values decreased from 0.083 to 0.013 meq NaOH/100g for PPR treatment ratios of 0 %–100 % PPR, respectively. The FQ and FI values peaked at 98.7 % and 1.19 for the 50 % PPR treatment before decreasing to 58.3 % and 0.098, respectively, at 100 % PPR. Sensory evaluation revealed improved overall flavor quality scores with increasing PPR, reaching a maximum of 44.8 at 50 % PPR before reducing to 34.0 at 100 % PPR. Principal component analysis clustered samples according to the PPR treatment ratio, fermentation duration, and quality parameters measured. Optimal conditions for enhanced nib acidification, fermentation quality, and flavor attributes were identified at 50 % PPR and 6-days fermentation using the response surface methodology. Overall, the study demonstrates the potential of PPR as a pulp pre-conditioning technique to improve drying time and enhance the quality of cocoa beans.